Arab family studies : critical reviews - Joseph, Suad (Gender, culture, and politics in the Middle East., 2018)
This review of the literature on Arab families captures the major theories, methods, and case studies carried out on Arab families over the past half to one century. The book offers a country by country critical assessment of the scholarship on Arab families.